2021
DOI: 10.1186/s12868-021-00683-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates sepsis-induced neuronal injury and cognitive impairment

Abstract: Background Sepsis is considered to be a high-risk factor for cognitive impairment in the brain. The purpose of our study is to explore whether sepsis causes cognitive impairment and try to evaluate the underlying mechanisms and intervention measures. Methods Here, we used cecum ligation and puncture (CLP) to simulate sepsis. Open field, Novel Objective Recognition, and Morris Water Maze Test were used to detect cognitive function, long-term potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(29 reference statements)
0
4
0
3
Order By: Relevance
“…21 In addition, metformin is known to exert a therapeutic effect on sepsis. Metformin appears to be a treatment option for postsepsis immunosuppression, 22 septic brain injury, 23 and sepsis-associated liver injury 24 ; therefore, metformin could be a useful agent against sepsis-related organ damage as well. 25 Various mechanisms, including oxidative stress, are involved in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, metformin is known to exert a therapeutic effect on sepsis. Metformin appears to be a treatment option for postsepsis immunosuppression, 22 septic brain injury, 23 and sepsis-associated liver injury 24 ; therefore, metformin could be a useful agent against sepsis-related organ damage as well. 25 Various mechanisms, including oxidative stress, are involved in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo foi identificado concentrações muito altas de citocinas, em contrapartida não foi encontrado aumento de proteínas especificas do cérebro e nem danos cognitivos. Tal resultado obtido contradiz resultados de outros estudos que correlacionam danos cognitivos desenvolvidos após a sepse (CHUNG et al, 2020;MAZERAUD et al, 2020;GOTZ et al, 2014;ANDONEGUI et al, 2018;QIN et al, 2021).…”
Section: Discussionunclassified
“…Conforme evidenciado nos artigos encontrados a sepse a longo prazo pode desencadear danos cognitivos Qin et al (2021),. usaram a ligadura e punção de ceco (CLP) para simular a sepse.…”
unclassified
“…Thus, inhibition of synaptic plasticity can affect learning and memory function. Investigators observed that presynaptic proteins synapsin (SYN), synaptophysin (SYP), postsynaptic density protein 95 (PSD 95), and N-methyl-D-aspartate receptor subunit 2B (NR2B), Amino-3-hydroxy-5-methy-4-isoxazole propionate (AMPA) receptor subunit (GluR1) were downregulated, and hippocampal LTP inhibition in SAE animals (Zong et al, 2019b;Qin et al, 2021). Lin et al found that microglia activation and…”
Section: Synaptic Plasticity Inhibitionmentioning
confidence: 99%